TRANSITIVITY ANALYSIS OF INDONESIAN ONLINE-NEWS HEADLINES ON EDUCATION ISSUE: FULL DAY SCHOOL - Ni Kadek Herna Lastari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
Full Day School issue became a debatable problem for the parliamentary, the education practitioners, teachers, school staff, parents, and students themselves. All written and online newspapers compete with each other to publish the news with various headlines. This qualitative study presented the finding of a transitivity analysis of online news headlines on the Education issue of Full Day Schools in Indonesia. The paper investigated the application of Halliday’s theory of Transitivity analysis or Systemic Functional Grammar for the representation of Full Day School’s response in Indonesia. This paper proposed to identify and explain how the issue of Full Day School was represented and thought through language application in online news headlines by reporters. This paper used a descriptive method to study the problem. Documentation method was used to collect data from the websites of tempo.co and kompas.com newspapers paper from the 13th to the 20th of July 2016. There were 8 headlines collected from those two-online news websites. The findings showed that the material process dominated the other processes which revealed that the issue of Full Day School was the actor and the main problem, which caused negative impacts on the goals. The findings also reveal that the headlines are formed by the perspective of the reporters’ grammatical choices of the headlines which could affect the readers’ opinion-making process.